El Lahar Tinguiririca: su significado entre los Lahares chilenos - Abele, Gerhard (Investigaciones Geográficas: Una mirada desde el sur, 1982)
The Tinguiririca lahar is an example of many similar landforms, which cover large surfaces 60th in andine valleys and the Chilean longitudinal depression. I t is smaller than other ones in Chile, but - at the same time - better conserved, offering good conditions for genetic, kinematic and geochronologic studies, respecting volcanic mudflows. From the genetic and kinematic point of view, the longitudinal lahar profile may be in two parts: a) An upper and middle accumulative area, with concave transverse profile; b) A low accumulative area; whose transverse profile is convexe. These two profiles could be explained by means of braking process in lateral parts, related to central parts, as a function of longitudinal distonces from the origin. From the geochronologic point of view, the lahar was between the Last Glaciation and Late Glacial times. Therefore, i t is more recent than other ones.